2017
DOI: 10.3892/ol.2017.6223
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin sensitizes human bladder carcinoma cells to TRAIL-mediated apoptosis

Abstract: Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL), a member of the TNF superfamily, has garnered interest as it is relatively non-toxic to normal cells, but selectively induces apoptotic cell death in multiple types of transformed or malignant cells. Bufalin is the major digoxin-like immunoreactive component of Sum Su, which is obtained from the skin and parotid venom gland of the toad. Bufalin is known to inhibit cell proliferation and induce apoptosis in a variety of cancer cells. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Among these effects, the anti-tumor activity of Bufalin has caught the attention of many researchers. A large number of studies have indicated that Bufalin has the inhibitory effect on many kinds of malignant tumors, such as liver cancer [25], colorectal cancer [26], bladder cancer [27], gallbladder cancer [28], pancreatic cancer [29] and gastric cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…Among these effects, the anti-tumor activity of Bufalin has caught the attention of many researchers. A large number of studies have indicated that Bufalin has the inhibitory effect on many kinds of malignant tumors, such as liver cancer [25], colorectal cancer [26], bladder cancer [27], gallbladder cancer [28], pancreatic cancer [29] and gastric cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…Bufalin is a bioactive polyhydroxysteroid isolated from Venenum Bufonis, also called Chan Su, a well-known traditional Chinese medicine widely used in cancer treatment in China [ 4 , 23 ]. Recent studies have shown that bufalin has anti-cancer activity in various cancers, such as breast cancer [ 24 ], osteosarcoma [ 5 ], colon cancer [ 11 , 25 ], lung cancer [ 26 ], pancreatic cancer [ 27 ], bladder cancer [ 28 ] and hepatocellular carcinoma [ 9 ]. Studies had found that bufalin inhibits GC proliferation, induces apoptosis and reverses cisplatin resistance [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence indicates that cancer cells can develop resistance to TRAIL if they lose the ability to express death receptors or exhibit constant activation of anti-apoptotic pathways 9, 10. Certain malignant cells are resistant to TRAIL, including bladder cancer cells 11-13. Therefore, identifying effective agents capable of overcoming TRAIL resistance in bladder cancer cells is necessary.…”
Section: Introductionmentioning
confidence: 99%